Analisis dan Implementasi Server Storage Berbasis Infrastructure as a Service Pada Laboratorium Komputer FTI UKSW Menggunakan EyeOS - Wilopo Liem Bob; Wiwin Sulistyo (AITI, 2016)
Faculty of Information Technology has a server in each laboratory which has different file stored and located in different location. Storage system in Faculty of Information Technology Satya Wacana Christian University labs has a problem, that is needed file sharing that is used on laboratory which had different location for class purposes. The problem would be happened that caused long distance and take much time just to get a file for learning in class. Cloud computing system designed for that problem, with using proxmox as a virtual manager and EyeOS as cloudmanagement, this system would solve the data centralization problem because all of laboratory files and documents for class activity would be placed into one cloud storage and able to accessed with any communication media tools. Cloud has a SSL encryption security system so that file which located on cloud would be secured because it was encrypted. Final result from this research would obtain a cloud server which used as centralized storage places and accessible for global or local purposes.